2019
DOI: 10.1111/apt.15094
|View full text |Cite
|
Sign up to set email alerts
|

Increased prevalence of anti‐TNF therapy in paediatric inflammatory bowel disease is associated with a decline in surgical resections during childhood

Abstract: Summary Background Anti‐tumour necrosis factor‐α (anti‐TNF) therapy use has risen in paediatric‐onset inflammatory bowel disease (PIBD). Whether this has translated into preventing/delaying childhood surgery is uncertain. The Wessex PIBD cohort was analysed for trends in anti‐TNF‐therapy and surgery. Aim To assess patients diagnosed with PIBD within Wessex from 1997 to 2017. The prevalence of anti‐TNF‐therapy and yearly surgery rates (resection and perianal) during childhood (<18 years) were analysed (Pearson'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 54 publications
(120 reference statements)
2
29
0
Order By: Relevance
“…A recent study in the Southampton Children’s Hospital showed a decreased surgical rate between 2007 and 2017 from 7.1% to 5.1%, respectively, which was most pronounced in patients with CD (8.9% vs. 2.3%). Although the resection rate in patients treated with anti-TNF therapy was not significantly different from those who were not, a multivariate regression analysis showed anti-TNF therapy prevalence per year was the only significant predictor associated with reduction in surgical resection rate [13].…”
Section: Resultsmentioning
confidence: 99%
“…A recent study in the Southampton Children’s Hospital showed a decreased surgical rate between 2007 and 2017 from 7.1% to 5.1%, respectively, which was most pronounced in patients with CD (8.9% vs. 2.3%). Although the resection rate in patients treated with anti-TNF therapy was not significantly different from those who were not, a multivariate regression analysis showed anti-TNF therapy prevalence per year was the only significant predictor associated with reduction in surgical resection rate [13].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, there was no change in the rate of hospitalization before and after treatment among the children receiving biologic therapy, except for patients that were treated during 2016-2019. In concurrence with the reported increase in the incidence of pediatric IBD [30], the rate of biologic therapy and, specifically, anti-TNF-α agents, is increasing worldwide among both adults and children [31][32][33][34] and is now the cornerstone in the treatment of IBD. This trend caused a significant increase in healthcare costs attributable to IBD [35][36][37].…”
Section: Discussionmentioning
confidence: 82%
“…Over 25% of all paediatric CD patients are now escalated to anti-TNF and other biological therapies, 10 but approximately one in three patients will not have a sustained response to maximal medical therapy. 11,12 The gastrointestinal microbiome has an important role in mucosal immune homoeostasis and evidence from epidemiological studies and mouse models suggest it is involved in the pathogenesis of CD.…”
Section: Introductionmentioning
confidence: 99%
“…Inducing and maintaining mucosal healing is a major challenge. Over 25% of all paediatric CD patients are now escalated to anti‐TNF and other biological therapies, 10 but approximately one in three patients will not have a sustained response to maximal medical therapy 11,12 …”
Section: Introductionmentioning
confidence: 99%